Ions, the Movement of Water and the Apoptotic Volume Decrease - Bortner, Carl D.; Cidlowski, John A. (Frontiers in Cell and Developmental Biology, 2020)
The movement of water across the cell membrane is a natural biological process that occurs during growth, cell division, and cell death. Many cells are known to regulate changes in their cell volume through inherent compensatory regulatory mechanisms. Cells can sense an increase or decrease in their cell volume, and compensate through mechanisms known as a regulatory volume increase (RVI) or decrease (RVD) response, respectively. The transport of sodium, potassium along with other ions and osmolytes allows the movement of water in and out of the cell. These compensatory volume regulatory mechanisms maintain a cell at near constant volume. A hallmark of the physiological cell death process known as apoptosis is the loss of cell volume or cell shrinkage. This loss of cell volume is in stark contrast to what occurs during the accidental cell death process known as necrosis. During necrosis, cells swell or gain water, eventually resulting in cell lysis. Thus, whether a cell gains or loses water after injury is a defining feature of the specific mode of cell death. Cell shrinkage or the loss of cell volume during apoptosis has been termed apoptotic volume decrease or AVD. Over the years, this distinguishing feature of apoptosis has been largely ignored and thought to be a passive occurrence or simply a consequence of the cell death process. However, studies on AVD have defined an underlying movement of ions that result in not only the loss of cell volume, but also the activation and execution of the apoptotic process. This review explores the role ions play in controlling not only the movement of water, but the regulation of apoptosis. We will focus on what is known about specific ion channels and transporters identified to be involved in AVD, and how the movement of ions and water change the intracellular environment leading to stages of cell shrinkage and associated apoptotic characteristics. Finally, we will discuss these concepts as they apply to different cell types such as neurons, cardiomyocytes, and corneal epithelial cells.